India's ongoing rooftop solar journey 2017-2022 - Mohua Mukherjee (The Oxford Institute for Energy Studies, 2022)
India is often taken as a microcosm for much of the developing world because people living in many different circumstances in the country are representative of what is found in large parts of the developing world. This is particularly relevant for clean technologies that are consumer-led and therefore require an upfront financial contribution from consumers, such as rooftop solar which is the subject of this paper. India's early experience with its nascent rooftop solar market has revealed two significant barriers to market growth that are directly linked to (i) equity and political economy factors and (ii) institutional factors in the electricity distribution sector. Unlike ground-mounted solar, rooftop photovoltaic (PV) requires individual consumers to make an investment in the hardware. The affordability of clean technologies is still a major issue in India, even though global rooftop PV prices have been tumbling over the past decade and rooftop PV is one of the most mature technologies. As a result, only the richest commercial and industrial (C&I) consumers have access to rooftop solar under the initial support schemes. In addition to equity, the institutional role of the electricity distribution sector in the growth of the rooftop sector is another barrier. The electricity distribution tariffs in Indian states are used as an income redistribution tool. The political economy of this aspect is very sensitive, and the central government's role is limited since the electricity distribution sector is controlled by the elected governments in each of the 28 states. Furthermore, distribution companies (discoms) are bundled meaning that in addition to owning and operating distribution grids, they are retailers responsible for customer service delivery and payment collection. As the growth of grid-connected solar rooftops could affect the financial viability of these companies, they have a tendency to resist or slow down penetration of rooftop solar PV, unless incentives are provided, enabling discoms also to benefit from the deployment of these resources. The best solution to reforming the distribution sector and possibly privatizing discoms is unlikely to happen in the near future. Therefore, second-best solutions must be identified in order to move ahead with rooftop installations and achieve targets for deploying these resources in order to advance the clean energy transition.
Keywords: 330; Electricity Distribution Companies; Electricity Distribution Sector; Energy Transition; India; Rooftop Photovoltaic (PV)